Circular and Collaborative Economies as a Propulsion of Environmental Sustainability in the New Fashion Business Models - Fernandes, Solange (2018)
The objective of this work is to explore convergence and divergence between business models of circular and collaborative economies in fashion industry and the benefits to sustainable development. The methodological approach is exploratory through bibliographic review and case study of two business models. The first, Rent the Runway, makes use of the Services and Products System (PSS), being a circular model using eco-efficient services with the potential to replicate and to compete with the ‘fast-fashion’ industry. The case study was done using data from Rent the Runway website. The second, Wardrobe, a P2P platform whose study was conducted with personal information with the company co-founder Germanno Teles. Wardrobe business models have a high potential for scalability, as they can be replicated anywhere, have no physical inventory, as users own their clothes. Thus, circular economy is considered to be holistic and adaptive, representing an evolution of the linear economy through the perception and need of a new sustainable strategy in response to the environmental degradation caused by the traditional linear economy. Collaborative economy can be considered an environmentally sustainable socio-economic system, built through the use of digital networks to connect and share goods and products, as well as human, financial and physical capital.